Endothelial glycocalyx in health and kidney disease: Rising star or false Dawn?. Issue 12 (16th November 2017) - Liew, Hui; Roberts, Matthew A; MacGinley, Robert; McMahon, Lawrence P
Summary at a Glance: The endothelial glycocalyx on the surface of vascular endothelial cells, an early indicator of endothelial injury and a potential marker of vascular injury, could be demonstrated by a variety of methods of assessment, including novel optical approaches and might be a potential therapeutic target. ABSTRACT: The endothelial glycocalyx is a layer comprised of proteins and carbohydrates on the luminal surface of vascular endothelial cells, thought to have an important role in the health and function of the endothelium. Disrupted by various pathophysiological conditions and linked with clinical outcomes, it is increasingly recognized as an early indicator of endothelial injury and a potential marker of vascular injury. In this review, we discuss current methods of assessment (including novel optical approaches), evidence for its use as a marker of vascular disease and its potential role in relation to microalbuminuria and glomerular endothelial dysfunction. Therapeutic strategies for restoration of the glycocalyx following injury are also explored.